Evaluation of Stiffness Degradation Curves from in Situ Tests in Various Soil Types - Godlewski T. (Archives of Civil Engineering, 2018)
Increasingly complex design systems require an individual approach when determining the necessary design parameters. As soils are characterized by strong strain-dependent nonlinearity, test methods used to characterize the subsoil should be carefully selected, in terms of their “sensitivity” as well as suitability for the analyzed type of problem. When direct measurements are not available, while design calculation models require specific parameters, indirect parameter estimation may be used. This approach requires calibration and validation of empirical correlations, based on well documented database of tests and case studies. One of the parameters often used, when analyzing soil-structure interaction problems, is the shear stiffness of the soil and its strain-dependent degradation. The aim of the article is to present the procedure for description and evaluation of soil stiffness based on field tests (CPTU, DMT and SDMT) and a large number of reference curves obtained from laboratory tests (TRX) for selected soil types. On the basis of the given algorithm, it is possible to obtain a stiffness module G0 value at any level of deformation, based on in-situ tests.